High sensitivity of HIV antibody screening tests may lead to longer time to diagnosis: a Case Report - Wang, Yuanfang; Luo, Lan; Deng, Jielun; Li, Xiaohan; Xie, Yi; Li, Dongdong (Frontiers in Medicine, 2025)
BackgroundThe fourth-generation human immunodeficiency virus (HIV) serology assay, which simultaneously detects the HIV-1 p24 antigen and HIV-1 antibodies, is available either in a combined format or as dual tests that differentiate between the p24 antigen and antibodies. Divergent detection methodologies require distinct confirmatory testing algorithms, which significantly impact the time to HIV infection.Case presentationIn this report, we present three cases where the HIV-1 p24 antigen tested reactive, while the HIV-1 antibody remained non-reactive in a dual testing scenario—despite both the combined test and the colloidal gold immunochromatographic assay (GICA) for HIV-1 antibodies yielding reactive results. Upon further analysis of subsequent laboratory procedures, we observed that due to the application of various complementary tests, the assay with high antibody sensitivity such as the GICA paradoxically resulted in a prolonged time to diagnosis, extending the diagnostic window for patients from 5 days to 11 days.ConclusionOur findings underscore the importance of prioritizing HIV-1 RNA testing in cases of discordant results between combined antigen/antibody testing, dual testing, and stand-alone antibody testing, particularly for patients who have not received pre-exposure or post-exposure prophylaxis.